STARCH AND CYCLODEXTRIN BASED ADSORBENTS FOR REMOVAL AND PRECONCENTRATION OF POLYCYCLIC AROMATIC HYDROCARBONS AND PHTHALATES IN WATER (2014)
The release of Polycyclic Aromatic Hydrocarbons (PAHs) and phthalates from anthropogenic sources into the aquatic environment is of public health concern. The C18 bonded silica and styrene-divinyl-benzene polymer adsorbents which are used for preconcentration and remediation of PAHs and phthalates polluted water are expensive and non-biodegradable. Hence, there is need to source for alternative adsorbents. Starch and cyclodextrin based polymers have been reported to be cheap and biodegradable, but have not been applied as adsorbents for PAHs and phthalates. In this study, starch and cyclodextrin based adsorbents were synthesised and employed for removal and preconcentration of PAHs and phthalates in water. Starch (15.0 g), β-cyclodextrin (12.5 g), and γ-cyclodextrin (8.0 g) were cross-linked with epichlorohydrin (EPI) (34.0-340.1 mM), 1,6-hexamethylene diisocyanate, (HDI) (7.04-70.4 mM), and 4,4-methylene diphenyl diisocyanate, (MDI) (7.04-70.4 mM) to produce EPI, HDI, and MDI cross-linked adsorbents [EPI-starch, EPI-β-cyclodextrin, and EPI-γ-cyclodextrin; HDI-starch, HDI-β-cyclodextrin, and HDI-γ-cyclodextrin; and MDI-starch, MDI-β-cyclodextrin, and MDI-γ-cyclodextrin]. The adsorbents were characterised using infrared spectrophotometry, Brauner-Emmet-Teller surface analysis, Scanning Electron Microscopy (SEM) and elemental analysis. Effects of time, temperature, and initial adsorbate concentration on the adsorption of PAHs (acenaphthylene, phenanthrene, fluorene, benzo(a)anthracene) and phthalates (dimethyl and diethyl phthalates) were studied using standard methods. Data generated were used to study the adsorption kinetics and thermodynamics of the adsorption process, and also fitted to four isotherm models. The adsorbents’ efficiencies were evaluated by their respective adsorption coefficients, dK . The preconcentration studies applied off-line column Solid Phase Extraction (SPE) standard procedure using the adsorbents (250 mg) as the solid phase and the adsorbents were validated by recovery studies and detection limit. The observed infra-red peaks of aromatic (3036, 1598, and 819 cm–1), amine (1721 and 751 cm–1), and carbonyl (1671 cm–1) functional groups in the adsorbents indicated successful cross-linking process. Surface areas of adsorbents (3.3-40.4 m2/g) were higher than those of native starch (1.0 m2/g) and cyclodextrins (0.7 m2/g). Increment in porosity UNIVERSITY OF IBADAN LIBRARY iii was observed from SEM images, which confirmed the enhancement of surface area of adsorbents. The adsorbents had higher carbon content (42.7-59.9%) and lower hydrogen content (5.7-7.6%), an indication of increased hydrophobicity. The adsorption data for PAHs and phthalates were best described by pseudo-second order kinetics (r2>0.996), which confirmed that surface adsorption was the rate-limiting step. The adsorption free energy values were negative, and thus confirmed the spontaneity of the adsorption process. Freundlich isotherm (r2>0.746) best described PAHs adsorption, an indication of multilayer adsorption; while phthalate adsorption was best fitted by Langmuir isotherm (r2>0.882), which was suggestive of monolayer adsorption. The log dK values of the adsorbents (4.0-5.0 for PAHs and 2.7-3.0 for phthalates) indicated good sorption efficiency. The values of recoveries (71.7-126.0% for PAHs and 81.5-104.6% for phthalates) and detection limit (0.9–153.4 ng/L for PAHs and 78.1-117.3 ng/L for phthalates) indicated high analytical performance for SPE preconcentration method using the adsorbents. Starch and cyclodextrin based adsorbents were effective in the removal and preconcentration of polycyclic aromatic hydrocarbons and phthalates in water; and hence are potential alternatives for the control of these chemical pollutants. Keywords: Cross-linked starch, Cyclodextrin based adsorbents, Solid phase extraction, Polycyclic aromatic hydrocarbons, Phthalates Word count: 497